Influência de aparelhos fotoativadores nas propriedades mecânica e química de cimentos resinosos fotopolimerizáveis em diferentes cores - Wobido, Amanda Ribeiro (2020)
The aim of this study was to evaluate the influence of light curing units of light-cured resin cements in different shades by degree of conversion (DC), Knoop hardness (KH) and elastic modulus (E). One lithium dissilicate ceramic disc (0.5mm thickness X 12mm diameter) was prepared and used to attenuate the light. Four resin cements were tested in different shades: Variolink Esthetic LC (shades L+ and W+, Ivoclar Vivadent), RelyX Veneer (shades B0.5, A1 and OW, 3M ESPE), NX3 Nexus LC (shades Yellow, Opaque White and Bleach, Kerr) and AllCem Veneer (shades A3, E-bleach and WO, FGM). The cement discs were made in a matrix (0.7mm tickness X 10mm diameter) and polymerizaded through a ceramic disc by five light curing units: Valo (Ultradent), Grand Valo (Ultradent), Elipar DeepCure (3M ESPE), Bluephase N (Ivoclar Vivadent) and Radii Xpert (SDI) (n=10). After 24h of preparation, the cement discs were evaluated for degree of conversion, Knoop hardness and elastic modulus. The measurements were made in the central and peripheral areas. The colorimetric analysis and opacity were measured for each cement shade to characterize and relate with the other material properties. The central measurements were analysed by ANOVA two-way and Tukey’s test. The peripheral area were compare to the central with Student’s T test. Pearson correlation test was performed to correlate degree of conversion and Knoop hardness, following by opacity, whiteness index and degree of conversion correlation. There was a statistic difference between the cement shades and the LCU for degree of conversion, Knoop hardness and elastic modulus (p<0.001). The central area presented higher properties than peripheral area for all cements polymerized by Radii Xpert. There was a positive correlation between opacity and degree of conversion (p<0.001; correlation coefficient = 0.453). In conclusion, the light curing unit and the cement shade affect the properties of light-cured resin cements. Only Radii Xpert showed lower values for all the properties in the peripheral area.